Anti‐adhesive effects of sialic acid and Lactobacillus plantarum on Staphylococcus aureus in vitro. Issue 1 (22nd November 2020) - Lu, Yingying; Yang, Yuzhuo; Liu, Lihua; Yu, Tianshu; Zhao, Jingjing; Liu, Libo; Li, Chun
Abstract: Staphylococcus aureus (S. aureus) is a common food‐borne pathogen that causes severe diseases after adhesion to epithelial cells. Lactobacillus inhibits pathogenic bacterial adhesion and infection. In addition, sialic acid (SA) is widely known for its beneficial biological functions. A new way of reducing the occurrence of diseases and curbing the overuse of antibiotics is ingesting prebiotics and probiotics that regulate the intestinal flora. In this study, we first evaluated the anti‐adhesive effects of several strains of Lactobacillus on S. aureus . The study revealed that the S. aureus adhesion was inhibited by all the strains of Lactobacillus . Besides, the rate of inhibition by L. plantarum Z‐4 was significantly higher than other Lactobacillus species . We then investigated the effects of different SA concentrations (40, 100, 150, 200, and 260 μg/ml) on the growth and adhesion characteristics of L. plantarum and S. aureus . The results showed that SA influences bacterial adhesion by regulating the bacteria's growth characteristics. Finally, the effects of SA combined with Lactobacillus on the adhesion of S. aureus were assessed by competition, exclusion and displacement methods. SA with a concentration of 260 μg/mL combined with L. plantarum had the highest inhibition effect on the competition assays. In addition, the expression of S. aureus adhesion‐related genes was reduced. This provides a new perspective on the application of SA and/or L. plantarum and its potential to resist adhesion of S. aureus . Abstract : This study evaluated the effects of sialic acid (SA) combined with Lactobacillus on the adhesion of S. aureus by three ways: competition, exclusion and displacement. It was found that 260 μg/ml SA combined with L. plantarum had the higher inhibition effect in the competition assays. As shown in the figure, compared with the control group (Figure A), after adding 260 μg/ml SA and L. plantarum Z‐4 (Figure B), the number of fluorescently labeled S. aureus adhered to the cells was significantly reduced.